2007
DOI: 10.1300/j370v23n01_02
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Evaluation of Small Group Challenging Horizons Program (CHP)

Abstract: This study examined the efficacy of an after-school program, the Challenging Horizons Program (CHP), that met four days a week and focused on improving organization, academic skills, and classroom behavior. The CHP was compared with a community control that included involvement in a district-run after-school program that met one to three days a week and focused on preparation for standardized testing. Participants were 48 middle-school youth, referred as experiencing a combination of learning and behavior prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 24 publications
0
21
0
6
Order By: Relevance
“…It is likely that by preparing families, the negative effects of the transition can be minimized, placing children with ADHD on a better developmental trajectory. School-based interventions that specifically target middle school students at-risk for failure and with ADHD have been tested and appear promising (Evans, Langberg et al, 2005; Langberg et al, 2006; Molina et al, in press). However, to our knowledge there is no published research testing the effectiveness of interventions implemented between elementary and middle school.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that by preparing families, the negative effects of the transition can be minimized, placing children with ADHD on a better developmental trajectory. School-based interventions that specifically target middle school students at-risk for failure and with ADHD have been tested and appear promising (Evans, Langberg et al, 2005; Langberg et al, 2006; Molina et al, in press). However, to our knowledge there is no published research testing the effectiveness of interventions implemented between elementary and middle school.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the timing and duration of the treatment has varied across studies. Two studies evaluated the benefit of the CHP offered only during the fall term (16 weeks and 10 weeks, respectively; see Langberg et al, 2006; Molina et al, 2008); although the program was offered 4 days per week in the Langberg and colleagues study and only 2 days per week in the Molina and colleagues study. In the two studies conducted by Evans and colleagues the program was provided 3 days per week for 22 weeks (November–May; Evans, Axlerod, & Langberg, 2004) or for the entire academic year (Evans, Langberg, Raggi, Allen, & Buvinger, 2005).…”
Section: The Challenging Horizons Programmentioning
confidence: 99%
“…The benefits of family interventions reported in the two Barkley and colleagues studies (1992, 2001), as well as the success of the FCU (Stormshak et al, 2010), suggest that enhancing the family interventions provided as part of the CHP may increase the benefits for the participants. In the study by Langberg and colleagues (2006) there were no parent interventions, the study by Molina and colleagues (2008) included three 2-hour parent meetings, and the Evans, Langberg, and colleagues studies (2005) included 90-minute monthly parent meetings. Engaging parents and providing family-focused interventions ahead of the period of academic decline in the second half of the academic year may optimally take advantage of both the school-based and family interventions that have been supported for adolescents with ADHD.…”
Section: The Challenging Horizons Programmentioning
confidence: 99%
“…Another school-based intervention for middle school students with ADHD is the CHP. Preliminary studies have indicated benefits for both academic and social functioning for these youth (Evans, Axelrod, & Langberg, 2004;Evans, Langberg, Raggi, Allen, & Buvinger, 2005;Evans, Serpell, Schultz & Pastor, 2007;Langberg et al, 2006;Molina et al, 2008). In one version of the CHP, participants attend an after-school program two to three times per week for approximately 2 h each day at their respective schools.…”
Section: School-based Interventions Targeting Disorganizationmentioning
confidence: 99%